2021
DOI: 10.1080/19475705.2021.1875058
|View full text |Cite
|
Sign up to set email alerts
|

The failure characteristics around shallow buried tunnels under rainfall conditions

Abstract: The instability of weak surrounding rock around shallow buried tunnels induced by rainfall is a challenge for tunnel engineering and threatens construction safety. To reveal the influence of rainfall on the rock surrounding a tunnel, the results of experiments on the failure of surrounding rock under different rainfall intensities and durations using a self-developed test system are presented. First, the stress and seepage behaviors of the surrounding rock under rainfall were analysed, and the results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Xia et al [138] calculated the insulation layer thickness under different working conditions by combining theoretical analysis with numerical simulation of temperature field. Based on the heat conduction theory of multilayer cylinder wall and combined with the Stephen formula, the implicit expression of the theoretical formula for the thickness of double-layer insulation layer was also derived, which is shown in Equation (11).…”
Section: Thermal Insulation Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al [138] calculated the insulation layer thickness under different working conditions by combining theoretical analysis with numerical simulation of temperature field. Based on the heat conduction theory of multilayer cylinder wall and combined with the Stephen formula, the implicit expression of the theoretical formula for the thickness of double-layer insulation layer was also derived, which is shown in Equation (11).…”
Section: Thermal Insulation Structurementioning
confidence: 99%
“…It is reported that the temperature in Qinling Line I tunnel is 31~42.1 • C at the depth of 1000~1600 m [10], and the highest temperature in the Sun Village Tunnel in Yunnan Province is up to 43 • C [11]. The area along Sichuan-Tibet Railway belongs to the Mediterranean-Himalayan tropical zone, among which there are about 15 tunnels evaluated to suffer geothermal disaster [12].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, many articles studied tunnel collapse by applying the modeling experiment (Barla, 2008;Yang et al, 2019;Liu et al, 2020;Hao et al, 2021;Wang et al, 2021;Lan et al, 2022;Li et al, 2022). The simulation experiment allows for a more intuitive understanding of the structure's failure process and a detailed investigation of its failure mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hydraulic characteristics of bimsoils are obviously different from those of homogeneous geo-materials. In addition, bimsoils of different regions and origins have different morphological and structural characteristics, which will ultimately result in different permeability and seepage characteristics (Kalender et al 2014;Zhou et al 2019;Qian et al 2020;Wang et al 2021bWang et al , 2021c. Hence, it is of great theoretical and practical significance to study the permeability and variable mass seepage characteristics of bimsoils under water-rich conditions.…”
Section: Introductionmentioning
confidence: 99%